2011
DOI: 10.1002/joc.2085
|View full text |Cite
|
Sign up to set email alerts
|

Annual precipitation reconstruction since AD 775 based on tree rings from the Qilian Mountains, northwestern China

Abstract: ABSTRACT:A millennium-long tree-ring-width chronology from the middle Qilian Mountains in northwestern China has been used to reconstruct annual precipitation variation (from the prior August to current July) since AD 775. The reconstruction explains 37.8% of variance of the observed data. Based on the mean and standard deviation of the reconstructed series, several prolonged severe dry and wet periods were indentified: drought spells in AD 1144-1154 (11 years) and 1925-1932 (8 years) and wet spells in AD 985… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 61 publications
7
52
1
3
Order By: Relevance
“…The centennial cycles identified in our study were possibly associated with the frequencies of solar variations (Stuiver and Braziunas, 1989;Raspopov et al, 2008). The cycles similar to the periodicities of 90-170 years have been found in other tree-ring reconstructions in China Gou et al, 2010;Y. Zhang et al, 2011).…”
Section: The Periodicity Of the Reconstruction And The Possible Forcisupporting
confidence: 86%
See 2 more Smart Citations
“…The centennial cycles identified in our study were possibly associated with the frequencies of solar variations (Stuiver and Braziunas, 1989;Raspopov et al, 2008). The cycles similar to the periodicities of 90-170 years have been found in other tree-ring reconstructions in China Gou et al, 2010;Y. Zhang et al, 2011).…”
Section: The Periodicity Of the Reconstruction And The Possible Forcisupporting
confidence: 86%
“…7b) in our reconstruction are typically associated with El Niño-Southern Oscillation (ENSO) (Allan et al, 1996); similar periodicities have been identified in other temperature and precipitation reconstruction series in China (Fang et al, 2009;Li et al, 2011a;Y. Zhang et al, 2011;Sun and Liu, 2012;Deng et al, 2013).…”
Section: The Periodicity Of the Reconstruction And The Possible Forcisupporting
confidence: 81%
See 1 more Smart Citation
“…specimens, and developed a 3500-year annual precipitation reconstruction for this region. Zhang et al [14], Chen et al [15], and Yang et al [16] presented long-term annual rainfall histories for the central-Qilian Mountains and the Hexi Corridor in the arid Northwest China, utilizing dendroclimatological methods in their studies. With the help of these precipitation reconstructions, it was suggested that associations exist between precipitation in northwest China and the temperature [13], El Niño-Southern Oscillation circulation (ENSO) [14], westerlies [15], and the Asian summer monsoon [16], and that further warming might contribute to an even greater moisture supply in the Northeastern Tibetan Plateau [13].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of autumnal precipitation variation is still limited and the related data still sparse [13][14][15][16]. Furthermore, occurrences of climatic extremes (i.e., droughts, floods, cloudy rain, and rainstorms) were reported to be frequent in China, with widespread effects [18].…”
Section: Introductionmentioning
confidence: 99%